Effect of Tool Holder Angles on Cutting Force When Machining Aerospace Material - K., Kadirgama (2009)
Cutting force is one of the main factors to be considered in CNC milling machine. Prediction models and optimum values are very important for the machinist to save number of cutting tools and reduce machining time. This paper discussed the effect of the two different angles (90° and 70°) of tool holder on cutting force when machining aerospace material (Hastelloy C-22HS) in two different environments (dry and flood). The 90o tool holder is suitable to be used in rough machining, milling casting part, internal facing with low accuracy and others. It can be used in the condition of high cutting speed, high feed rate and high axial depth. On the other hand, the 70o tool holder is more suitable for milling operation of final machining component, hard material, etc. Response surface method (RSM) was used to minimize the number of experiments. First order models were developed to optimize the machining parameters (cutting speed, federate and axial depth) and obtain the optimum cutting force. It observed that low value cutting parameters need to be used for 70° tool holders, meanwhile for 90° tool holders high value cutting parameters can be used. Both angle of tool holder not suitable be used in dry cutting since the cutting force produced very high for machining purpose.